Chemical, structural and hyperfine characterization of goethites with simultaneous incorporation of manganese, cobalt and aluminum ions - Alvarez, Mariana (2015)
To elucidate the influence of bi-substitution on the structural and hyperfine properties of goetites, two series of (Al,Co)- and (Mn,Co)-substituted goethites were synthesized in alkaline media by aging several ferrihydrites with different Al/Co and Mn/Co ratios. The samples were fully characterized by chemical analyses, X-ray diffraction (XRD) and Mössbauer spectroscopy; scanning electron microscopy (SEM), zeta potential and BET surface area measurements were also performed. All the solids presented only an α-FeOOH-like structure, with the exception of two preparations with high Co concentrations that developed two phases, goethite and small amounts of the Co-ferrite (CoFe2O4). The cell parameters in the Co-substituted goethites were markedly smaller than that of the pure sample indicating a oxidation of Co(II) to Co(III) before the incorporation step. In the Co+Mn series the metal substitution followed the trend Co~Mn, and in the Co+Al series the trend was Al>Co, and in both cases the incorporation of Co decreased the crystallite size of the samples. The metal-for-Fe incorporation changed the specific surface areas and the morphology of the acicular formed particles. Cobalt containing samples had the highest SSA, while Mn-containing samples had the lowest SSA. The IEP values of the bi-substituted samples were similar to that of pure α-FeOOH, but mono-substitution by Mn and Al diminished the isoelectric points. The low IEP values detected in Mn-goethite (5.8) and Al-goethite (5.2) could be respectively ascribed to an inhomogeneous distribution of Mn(III), and to the different basicity properties of the surface Fe-OH and Al-OH groups. The hyperfine magnetic field Bhf, increased quasi linearly with the incorporation of Co in both series. In the Co-Mn series the effect was attributed to variations in particle size distribution, in contrast the marked increase observed in the Co-Al series can be attributed to the decrease in the content of diamagnetic ion Al(III). The results indicate that simultaneous substitutions produce substantial changes in the structural, surface and hyperfine properties of goethites. As the characteristics of the dissolution and adsorption processes of the goethites greatly depend on particle size, BET areas and surface charge of the solids, the reported results will allow us to predict changes in the chemical reactivity and adsorption of the multi-substituted goethites. Also the data on hyperfine properties will help to elucidate the probable substitution in natural samples. The fact that Co-incorporation in bi-substituted samples greatly decreased the particle size increasing the specific surface area is an important parameter for technological applications in adsorption removal processes.